Youth sport specialization and overuse injury risk: a critically appraised topic - Chizuk, H. M.; Marshall, K.; Zipp, J.; Sardinia, W.; Zafron, M. L.; Leddy, J. J.; Pryor, R. R. (International Journal of Athletic Therapy & Training, 2025)
Context: It is important to identify factors that increase injury risk among youth sport participants, as injury and the fear of injury can prompt athletes to dropout of sport. Several cross-sectional studies found that sport specialization is associated with increased injury rates, specifically overuse injury, among youth sport participants. However, there is a need to critically appraise high-quality pieces of prospective evidence linking sport specialization to injury to guide clinical recommendations for clinicians interacting with youth athletes.